Biological agent in prevention of ocular recurrence in Behçets disease: a case report - Adnan, Ismail A; Kharelo, Sitaula R; Biswas, J (Nepalese Journal of Ophthalmology, 2019)
Introduction: Ocular involvement in Behçets disease (BD) is characterized by recurrent inflammatory attacks leading to poor long-term visual prognosis. The development of biologic agents has heralded a new era in the management of BD uveitis enabling more targeted immune modulation with greater efficacy and has now become the first line agents.Objective: To report a case of young gentleman with Behçets disease whose ocular recurrence was controlled with injection Adalimumab.Case: A 31-year-old male with recurrent oral and genital ulcers with bilateral recurrent uveitis was diagnosed as bilateral ocular Behçet’s disease based on positive HLA B51typing and ferning pattern in FFA. He was on oral Prednisolone and Cyclosporine and was advised for biological agents. On presentation to us, he had anterior uveitis with pseudophakia and secondary open angle glaucoma in right eye and posterior sub capsular cataract in left eye. After starting Inj Adalimumab with oral Methotrexate, he ocular inflammation was under control and patient underwent uneventful cataract surgery in left eye. Over 1-year follow-up, the patient is on remission, on injection Adalimumab with the steroid tapered off.Conclusion: Biological agents like Adalimumab is effective in controlling recurrences in Behçet’s disease.